Is co-branding a leversor of purchase decisions? - Ratu Jennifer Cikita; R.A. Marlien (Jurnal Mantik, 2023)
It is important for sellers of a product to make consumers buy their products. Aerostreet - Rown Division continues to experience improvement from 2018-2020, with a co-branding strategy and collaboration with Aerostreet. This study aims to examine the effect of co-branding, price, promotion on purchasing decisions. The population in this study were all Aerostreet and Rown Division buyers whose exact number was not known, while the samples taken were 83 respondents, using a purposive sampling technique. The findings show that co-branding has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, and promotion has a positive and significant effect on purchasing decisions.